CURRENT APPROACH TO DEVELOPMENT OF BIOSIMILAR PRODUCTS CONTAINING MONOCLONAL ANTIBODIES AS AN ACTIVE SUBSTANCE – NON-CLINICAL AND CLINICAL STUDIES OF THE FIRST RUSSIAN RITUXIMAB BIOSIMILAR, ACELLBIA® - S. M. Alekseev; K. D. Kaplanov; R. A. Ivanov; E. V. Chernyaeva (Исследования и практика в медицине)
Objective. Evaluation of pharmacokinetics, pharmacodynamics, safety and efficacy of rituximab biosimilar (Acellbia,  BIOCAD, Russia) used as  monotherapy in patients with indolent B-cell non-Hodgkin’s lymphoma in comparison with the parameters of innovator rituximab – MabThera.Materials and methods. 92 patients (aged 18 years and older with diagnosed CD20-positive follicular non-Hodgkin’s lymphoma, stage II-IV by Ann Arbor, 1-2 histologic grade, or marginal zone lymphoma) were enrolled into the study. Patients were randomised in 1:1 ratio to receive 375 mg/sq.m of Acellbia or MabThera on days 1, 8, 15 and 22.Results. Overall response rate in both arms was equivalent: 39.52% in BCD-020 arm and 36.57% of patients in RTX arm (p=0.8250). Within the first week after a single infusion of Acellbia or MabThera, the level of  CD19 and CD20-positive cells rapidly decreased to almost undetectable values without any obvious recovery by the end of observation (upon intergroup comparison p>0.05 at all specified time points). 90% CI for the geometric mean of a Acellbia/MabThera  AUC0-t ratio fell within standard bioequivalence range 80-125% (80.1-118.2% for the ratio of AUC0-168 after a single dose). Within the whole study period  the frequency of AEs, including severe AEs (grade 3-4), associated with the use of monotherapy, were equal in both arms without any significant differences. Conclusions. Acellbia is non-inferior to MabThera in terms of efficacy, pharmacokinetics, pharmacodynamics and immunogenicity. Acellbia was well tolerated, with the safety profile comparable with MabThera’s parameters.